The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1073/pnas.1710257114
|View full text |Cite
|
Sign up to set email alerts
|

Disruption and rescue of interareal theta phase coupling and adaptive behavior

Abstract: Rescuing executive functions in people with neurological and neuropsychiatric disorders has been a major goal of psychology and neuroscience for decades. Innovative computer-training regimes for executive functions have made tremendous inroads, yet the positive effects of training have not always translated into improved cognitive functioning and often take many days to emerge. In the present study, we asked whether it was possible to immediately change components of executive function by directly manipulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 40 publications
1
62
0
Order By: Relevance
“…There is evidence that rhythmic stimulation in the theta range delivered to frontal areas can modulate behavioral performance in humans. One recent study found that 6-Hz transcranial alternating current stimulation over midline and the lateral frontal cortex improved executive function when synchronized, and reduced executive function when desynchronized (11). Many researchers have reported improved learning and performance with direct current frontal stimulation (54), although these results are mixed (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that rhythmic stimulation in the theta range delivered to frontal areas can modulate behavioral performance in humans. One recent study found that 6-Hz transcranial alternating current stimulation over midline and the lateral frontal cortex improved executive function when synchronized, and reduced executive function when desynchronized (11). Many researchers have reported improved learning and performance with direct current frontal stimulation (54), although these results are mixed (55).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, human studies have provided evidence that increases in theta current density are correlated with increased metabolism in the ACC (10). When the ACC receives theta stimulation that is in phase with stimulation of a lateral frontal area, there is an improvement in measures of executive function (11). Based on these findings, we wanted to explore the potential causal relationships between increased midfrontal theta and white matter change.…”
mentioning
confidence: 99%
“…To correct for changes in individual performance between sessions, we referenced performance to that in the baseline block in each session. To test whether our results could be confounded by performance fluctuations in this baseline level between test days, we performed test – retest reliability analyses, comparing baseline results across different testing days 52 . We found that individual subjects’ performance across sessions were significantly correlated in both Experiment 1 (Spearman’s Rhos = 0.48; P = 0.032) and Experiment 2 (Spearman’s Rhos = 0.52; P = 0.028), indicating the stability of individual differences across testing days.…”
Section: Resultsmentioning
confidence: 99%
“…Impairment of proper coupling may lead to disorders, such as AD, PD, epilepsy, schizophrenia and autism [9]. This has fueled research into noninvasive approaches to modulate and, possibly, re-adjust neural synchrony by transcranial alternating current stimulation (tACS) [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, relatively little is known regarding persistent physiological effects of tACS, i.e., aftereffects on neural activity that outlast the period of electrical stimulation. Lasting modulation of intrinsic oscillations (predominantly in the alpha-band) and persistent effects on task performance or mental state have been reported in noninvasive studies [14,[24][25][26][27]. By contrast, studies addressing electrophysiological aftereffects of tACS by invasive recordings have not yet been performed.…”
Section: Introductionmentioning
confidence: 99%